2021
DOI: 10.3390/jcm10051061
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Clinical Management of Patients with Primary Biliary Cholangitis—A Retrospective Multicenter Study from Germany

Abstract: Background: Clinical practice guidelines for patients with primary biliary cholangitis (PBC) have been recently revised and implemented for well-established response criteria to standard first-line ursodeoxycholic acid (UDCA) therapy at 12 months after treatment initiation for the early identification of high-risk patients with inadequate treatment responses who may require treatment modification. However, there are only very limited data concerning the real-world clinical management of patients with PBC in Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
3
5
0
Order By: Relevance
“…Biochemical non-response to UDCA is a well-known predictor of long-term histological progression [ 10 ]. UDCA response rates in our cohort were found to be generally similar to previous reports, yet higher in comparison to recent similar studies [ 21 , 22 ]. According to the Barcelona criterion, we have documented a non-response rate of 40.6%, while multicenter data from Portugal and Germany reported rates of 30.7% and 38.7%, respectively [ 21 , 22 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Biochemical non-response to UDCA is a well-known predictor of long-term histological progression [ 10 ]. UDCA response rates in our cohort were found to be generally similar to previous reports, yet higher in comparison to recent similar studies [ 21 , 22 ]. According to the Barcelona criterion, we have documented a non-response rate of 40.6%, while multicenter data from Portugal and Germany reported rates of 30.7% and 38.7%, respectively [ 21 , 22 ].…”
Section: Discussionsupporting
confidence: 90%
“…UDCA response rates in our cohort were found to be generally similar to previous reports, yet higher in comparison to recent similar studies [ 21 , 22 ]. According to the Barcelona criterion, we have documented a non-response rate of 40.6%, while multicenter data from Portugal and Germany reported rates of 30.7% and 38.7%, respectively [ 21 , 22 ]. In addition, when assessing response rates according to the Toronto criterion, we found a non-response rate of 28.1%, while a recently published German study found a non-response rate of only 16.2% according to this criterion [ 22 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Real world data confirmed the efficacy and safety of OCA in PBC with lower efficacy and reduced tolerability in patients with cirrhosis. 98 99 Notably, use of OCA was associated with an increase in hepatic decompensation in patients with compensated PBC cirrhosis. 100 which led to an update of the PBC label with a contraindication for use in patients with decompensated cirrhosis, a prior decompensation event or with compensated cirrhosis and evidence of portal hypertension.…”
Section: Nuclear Receptor Pathways As a New Therapeutic Frontiermentioning
confidence: 99%
“…Two studies investigated the current and future management of cholestatic liver diseases [ 4 , 5 ]. The first study retrospectively evaluated the real-world clinical management of patients with primary biliary cholangitis (PBC), according to the indications of the recent updated clinical guidelines.…”
mentioning
confidence: 99%